Ectoine and Hydroxyectoine from Halophilic Bacteria Isolated from Traditional Solar Saltern at Pejarakan Village, Buleleng Regency, Bali - I Putu Parwata; Siti Maryam; I Nyoman Tika (HAYATI Journal of Biosciences, 2022)
The increased use of ectoine and hydroxyectoine in cosmetics and pharmaceuticals has led to the increasing demand for these bioactive compounds. This study aims to investigate the production of ectoine and hydroxyectoine by halophilic bacteria isolated from traditional solar saltern at Pejarakan Village, Buleleng Regency, Province of Bali, Indonesia. The halophilic bacteria were grown from the brine and the sediment samples using Luria Bertani media. The production of ectoine and hydroxyectoine was determined by inoculating the bacteria in MM63 media containing 12% w/v NaCl. Ectoine and hydroxyectoine were then extracted from the bacterial cells using a mixture of methanol/chloroform/water (10/5/4). Finally, the ability of the bacteria to excrete ectoine and hydroxyectoine was investigated using the osmotic downshock technique. The results showed that a total of 88 halophilic bacteria have been isolated which showed varied salt tolerances from 0 to 27.5% w/v. Most of the bacteria (86 isolates) were able to grow in MM63 media, suggesting the potential of the bacteria producing ectoine and hydroxyectoine. Further investigation showed that 33 selected halophilic bacteria were able to produce ectoine and hydroxyectoine with levels of 9.1 to 301.8 mg/L and 3.9 to 122.1 mg/L, respectively. All the bacteria were also able to excrete ectoine and hydroxyectoine after the osmotic downshock process with levels of 9.8 to 277.5 mg/L and 14.3 to 122.7 mg/L, respectively. The best ectoine and hydroxyectoine-producing bacteria showed the closest homology relationship with Salinivibrio costicola and Salinivibrio kushneri. Our study has found several promising candidates for ectoine and hydroxyectoine producers.